Reliability and validity of a satisfaction questionnaire on virtual education in the coronavirus disease 2019 pandemic era aimed at cardiology faculty members - Bahram Mohebbi; Parham Sadeghipour; Feridoun Noohi; Majid Maleki; Mohammad Mehdi Peighambari; Saeid Hosseini; Ali Zahedmehr; Jamal Moosavi; Omid Shafe; Mohammad Javad Alemzadeh-Ansari; Melody Farrashi; Hamidreza Pouraliakbar; et al. (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: In the coronavirus disease 2019 pandemic era, clinical programs and mandatory hands-on activities have been supplanted by remote teaching to maintain the fundamental capabilities of medical training and to furnish medical students with quality education. Nonetheless, the satisfaction of faculty members with this training method in the current pandemic has yet to be assessed. The aim of this study was to design a Persian questionnaire with appropriate validity and reliability on cardiology professors' satisfaction level with virtual education. MATERIALS AND METHODS: In this cross-sectional study, a questionnaire was devised drawing upon scientific sources and Iranian medical educators' expertise. Seventeen faculty members in various specialties evaluated the questionnaire concerning face and content validity. Content validity was assessed through the calculation of the content validity ratio (CVR) (values >0.62 were considered acceptable) and the content validity index (CVI) (values >0.79 were considered acceptable), construct validity was evaluated through principal component factor analysis by the Kaiser-Meyer-Olkin (KMO) statistic and Bartlett's sphericity test, internal reliability was measured through the calculation of Cronbach's alpha coefficient, and consistency was appraised through the use of test-retest reliability at two different time points. RESULTS: The questionnaire had a reliability rate of 95%, indicating high internal validity. Concerning test-retest reliability, the intraclass correlation coefficient was 0.96 (P < 0.001), demonstrating relatively good stability. The CVI was 0.81, and the CVR was 0.85. The KMO measure of sampling adequacy was 0.954, indicating the acceptability of the degree of common variance among the all items. CONCLUSIONS: This Persian questionnaire on virtual education aimed at cardiology faculty members in the current pandemic with its low question count and appropriate domains had high reliability and validity. By knowing the level of professors' satisfaction with the new method of education, it is possible to take steps to better provide specialized medical education to cardiology residents.